2019
DOI: 10.1016/j.cortex.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Neural organization of speech production: A lesion-based study of error patterns in connected speech

Abstract: While numerous studies have explored single-word naming, few have evaluated the behavioral and neural correlates of more naturalistic language, like connected speech, which we produce every day. Here, in a retrospective analysis of 120 participants at least six months following left hemisphere stroke, we evaluated the distribution of word errors (paraphasias) and associated brain damage during connected speech (picture description) and object naming. While paraphasias in connected speech and naming shared unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…However, picture naming, unlike the word fluency task, involves selecting among competing alternatives (e.g., to name a picture of a cat, the competing alternative dog must be suppressed). Interestingly, a recent LSM study of word-level semantic errors in natural, connected speech found that increased errors were associated with temporal and inferior parietal damage, but not frontal damage ( Stark et al, 2019 ). Connected speech differs from confrontation or picture naming in allowing the subject to select alternative words or concepts, which reduces the burden of the task on selection abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, picture naming, unlike the word fluency task, involves selecting among competing alternatives (e.g., to name a picture of a cat, the competing alternative dog must be suppressed). Interestingly, a recent LSM study of word-level semantic errors in natural, connected speech found that increased errors were associated with temporal and inferior parietal damage, but not frontal damage ( Stark et al, 2019 ). Connected speech differs from confrontation or picture naming in allowing the subject to select alternative words or concepts, which reduces the burden of the task on selection abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Across the 27 subtests that comprise the CAT, we selected the spoken picture description task as our behavioural index of speech production abilities, with the goal of ensuring the ecological validity of our findings by assessing connected speech production (rather than single word production) in a setting that resembled those encountered in real-world scenarios more closely. Our decision was also motivated by recent efforts to characterise the complex nature of speech production, their deficits and neural correlates using samples of connected speech ( Stark et al , 2019 ; Alyahya et al , 2020; Ding et al ., 2020 ). The CAT spoken picture description task was administered to each patient and the spoken responses scored following standardized procedures described in the assessment battery manual.…”
Section: Methodsmentioning
confidence: 99%
“…Given the methodological constraints described above, it was not feasible to investigate, within the same study, all the grey or white matter regions that have previously been associated with speech production. For example, we did not examine temporal and parietal regions ( Stark et al , 2019 ; Forkel et al , 2020 ), the internal capsule ( Naeser et al 1982 ), the medial subcallosal fasciculus or the periventricular white matter area ( Naeser et al , 1989 ). Nor did we investigate the inferior fronto-occipital fasciculus or long segment of the arcuate fasciculus because a previous well-powered lesion study was unable to establish a significant relationship between persistent speech production impairments and damage to either of these white matter tracts after controlling for damage to the anterior segment of the arcuate fasciculus ( Fridriksson et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…V Baldo et al (2012) repetition 3 84 2 Døli et al (2020) repetition 12 21 3 Faroqi-Shah et al (2014) nonword repetition 5 31 4 Kümmerer et al (2013) repetition 3 100 5 Sul et al (2019) repetition 3 31 6 Xing et al (2016) repetition 3 32 Naming 1 Reem. S. W Alyahya et al (2018) verb naming 16 48 2 Juliana V Baldo et al (2013) naming 2 43 3 Døli et al (2020) naming 7 21 4 Faroqi-Shah et al (2014) picture naming 5 31 5 Gajardo-Vidal et al (2018a) naming 3 359 6 Harvey and Schnur (2015) naming relatedness effect 2 15 7 Lau et al (2015) object naming 9 280 8 Schwartz et al (2012) naming error 4 106 9 Stark et al (2019) naming error 34 57 …”
Section: Methodsmentioning
confidence: 99%